Industrial and intellectual capital clusters in the Baltic states - Alf Vanags; Julija Basarova; Nellija Titova (European Regional Science Association (ERSA), 2002)
Various recent developments, eg the 'new economic geography' as exemplified by say, Krugman, P. (1991) or work originating in the business literature (Porter 1998), point to industrial and intellectual capital clusters as key factors associated with economic development. Indeed recent evidence suggests that multiple clustering leads to higher regional economic development. This leads to the idea that clusters should be encouraged as for example in the Latvian context in Phare (2001), an idea that is explicitly supported by theoretical argument in Norman and Venables (2001). In this paper we explore and describe the geographic concentration of production and human resources in the three Baltic States and attempt to identify its determinants. In particular, we address the issues of industrial and human resource base restructuring in the Baltic States. For the investigation of the regions or districts of the Baltic countries and their industries a variety of statistical methods and measures are used, including cluster analysis and the location quotient method, which may be used to measure the concentration and importance of an economic activity in cluster regions relative to other selected territories. Work is in progress but the aim is to reveal the pattern and dynamics of industrial and intellectual clusters in the Baltic states since independence. Casual evidence suggests that economic activity is less concentrated in Lithuania than in either Latvia or Estonia. The paper seeks to establish more formally whether there are indeed significant differences between the three Baltic countries with respect to i) the extent of cluster formation in general, ii) differences in the extent to which clusters have emerged in particular industries, and iii) how these have changed over time. The territorial units of analysis employed in the research are counties in Lithuania and Estonia (10 and 15 respectively) and in Latvia districts (26 of them). The descriptive part of the paper develops the work of Francis (2000) and Rivza and Stokmane (2000). Having calculated the descriptive statistics the paper combines several theoretical approaches to measure and evaluate clusters. In particular we modify Davis and Weinstein (1998) model to apply it to the case of the Baltic States. Davis, D.R. and D.E. Weinstein (1998) "Market Access, Economic Geography, and Comparative Advantage: An Empirical Assessment"; NBER Working Paper W6787 Francis, I.(2000),"Basic Analysis of Riga's Economy"; 6th Nordic-Baltic Conference in Regional Science. Riga, Latvia, October 4-7 2000. Reports, pp.111-115 Krugman, P. (1991a) Geography and Trade; Cambridge: MIT Press Norman, V.D. and A.J. Venables (2001) "Industrial Clusters: Equilibrium, Welfare, and Policy"; mimeo, London School of Economics Phare project (2001) Support to Industrial Cluster Restructuring; News Letters, Riga, Latvia Porter, M.E. (1998) "Clusters and the New Economics of Competition"; Harvard Business Review, 76:6 Rivza, B. and I. Stokmane (2000), "Economic and Social Analysis of the Baltic Countries"; 6th Nordic-Baltic conference in Regional Science. Riga, Latvia, October 4-7 2000. Reports, pp.293-296
Keywords: 330